2021
DOI: 10.1177/17588359211011455
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected tumor reduction in metastatic colorectal cancer patients during SARS-Cov-2 infection

Abstract: Herein, we describe three patients affected by metastatic colorectal cancer (mCRC) experiencing infection by severe acute respiratory syndrome coronavirus 2 (SARS-Cov-2) and reduction of disease burden during coronavirus disease 2019 (COVID-19) course. Insights into tumor-associated angiotensin-converting enzyme (ACE)-2 expression and lymphocyte function suggest a correlation between host/SARS-Cov-2 infection and tumor burden reduction. This may shed new light into (a) the infection mechanism of SARS-CoV-2 vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 11 publications
1
27
0
Order By: Relevance
“…Despite the preliminary clues pointing towards the role of the virus in promoting tumor progression described here, rare instances of tumor burden reduction in three patients with colorectal cancer and disease remission in a patient with Hodgkin lymphoma following COVID-19 infection have been reported in the literature [67,68]. Although the over-exuberant immune response instigated by SARS-CoV-2 attacking the tumor cells could have led to this phenomenon [69], the complex role of autophagy in cancer (acting as a double-edged sword) should not be underestimated in interpreting these exceptional cases.…”
Section: Implications For Cancer Treatmentmentioning
confidence: 80%
“…Despite the preliminary clues pointing towards the role of the virus in promoting tumor progression described here, rare instances of tumor burden reduction in three patients with colorectal cancer and disease remission in a patient with Hodgkin lymphoma following COVID-19 infection have been reported in the literature [67,68]. Although the over-exuberant immune response instigated by SARS-CoV-2 attacking the tumor cells could have led to this phenomenon [69], the complex role of autophagy in cancer (acting as a double-edged sword) should not be underestimated in interpreting these exceptional cases.…”
Section: Implications For Cancer Treatmentmentioning
confidence: 80%
“…Pasin F et al reported, in a 20-year-old patient, the transient remission of refractory NK/T-cell lymphoma during COVID-19 infection, suggesting that SARS-CoV-2 may have an oncolytic effect [25]. Other authors report similar cases of the favorable evolution of hematological cancers or solid tumors during SARS-CoV-2 infection, but the number of such reports is very low, and no conclusion can be drawn [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Ottaiano et al [ 32 ] reported that (a) the tumor burden of three patients with metastatic colon cancer decreased unexpectedly following 2019-nCoV infection, (b) one patient with liver metastasis showed complete remission on CT scan 1 month after 2019-nCoV infection, and (c) two other patients infected with 2019-nCoV showed an unexpected decrease in their metastases one to three months later. These studies showed that 2019-nCoV has an inhibitory effect on colon cancer, and ORF3a may be the key responsible factor, which is consistent with our results.…”
Section: Discussionmentioning
confidence: 99%